The Spanish Civil War in ’Crónica’ (1929-1938) during the first year of the battle. The poetic photography as information and strategy - de las Heras Herrero, Beatriz (Revista General de Información y Documentación, 2020)
To make photography become a source of analysis of the past, it is necessary to transcend the illustrative facet of the visual. Recognising reasons and interpreting images are not the same thing. Interpreting forces the visual reader to transcend the sight and project the glance, and this is the ultimate aim of the article. The projection will be taken from a specific collection: The photographs published in the weekly publication Chronicle (1929-1938) from July to December 1936, coinciding with the first six months of the Spanish Civil War. And we will use a methodology based on three phases: the first one consists of cataloguing individually each of the 931 photographs which covered the pages of the publication during the period of study. The second one is the creation of percentage profiles based on the quantitative results with the intention of discovering a trend. The third phase is the interpretation of this result with the intention of recording those camouflaged performances which allow us to extract information included in the snapshot but which is blurred if we apply a distracted gaze. Therefore, our aim is to launch a curious look on the photographs published in Chronicle between July and December 1936.